2023
DOI: 10.1002/oby.23643
|View full text |Cite
|
Sign up to set email alerts
|

Children's rates of BMI change during pre‐pandemic and two COVID‐19 pandemic periods, IQVIA Ambulatory Electronic Medical Record, January 2018 Through November 2021

Abstract: Objective Many U.S. youth experienced accelerated weight gain during the early COVID‐19 pandemic. Using an ambulatory electronic health record dataset, we compared children's rates of BMI change in three periods: prepandemic (January 2018‐February 2020), early pandemic (March‐December 2020), and later pandemic (January‐November 2021). Methods We used mixed‐effects models to examine differences in rates of change in BMI, weight, and obesity prevalence among the three per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This finding is similar to a recent study conducted with a much larger cohort of patients from the IQVIA’s AEMR database. 14 Although the etiology of the greater increase in BMI early in the pandemic versus later in the pandemic is likely multifactorial, the reintegration of children from the home to the preschool and school environments in the Late Pandemic period could be a possible association. Brazendale et al have postulated the “Structured Days Hypothesis,” suggesting that obesity-related behaviors, including sleep, physical activity, diet, and sedentary behaviors, are positively regulated when children are part of more structured days (similar to school environment) versus unstructured time as during the summer.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to a recent study conducted with a much larger cohort of patients from the IQVIA’s AEMR database. 14 Although the etiology of the greater increase in BMI early in the pandemic versus later in the pandemic is likely multifactorial, the reintegration of children from the home to the preschool and school environments in the Late Pandemic period could be a possible association. Brazendale et al have postulated the “Structured Days Hypothesis,” suggesting that obesity-related behaviors, including sleep, physical activity, diet, and sedentary behaviors, are positively regulated when children are part of more structured days (similar to school environment) versus unstructured time as during the summer.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis that youth assessed during the pandemic would gain more weight and adiposity than youth examined before the pandemic was based on literature demonstrating that youth gaining excess weight shortly after the onset of the pandemic [ 16 , 18 , 22 , 23 , 24 , 25 , 26 , 27 ] was in part due to a reduction in their physical activity in the same time period [ 13 , 14 , 19 , 26 , 28 ]. However, more recent data suggest that there was a rapid increase in the rates of obesity at the beginning of the pandemic that slowed later in the pandemic [ 35 ]. Our sample of pandemic data ranged from August 2020 to October 2021, thereby missing the first several months of the pandemic due to COVID-19 safety restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…The average of the three height measurements and measured weight were used to calculate BMI. BMIz scores were computed according to the CDC standards for age and sex [ 35 ]. Adiposity (percent fat mass) and lean mass (kg) were measured using dual energy X-ray absorptiometry (iDXA system, GE Healthcare, Madison, WI, USA), which is a validated body composition measure in youth [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a study that echoes our findings, a school-based program in Isparta Province, Turkey, showed that improvements in the rates of overweight and obesity that had occurred since 2005 were suddenly reversed, with 2021 numbers being higher than any they had previously observed [ 16 ]. A study relying on a large, common electronic medical record in the USA found that BMI increased very quickly during the early pandemic, but then stabilized or even improved slightly later in the pandemic [ 15 ]. A probabilistic annual national sample from Peru showed that the proportion of children with obesity had increased from 6.4% to 7.8% between 2019 and 2021 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%